The Exotic Beauty of Karst Morphology of Langgun Island and Geotourism Potential of Langkawi Island, Malaysia - Cahyaningsih, Catur; Khairunisya (UIR PRESS, 2024)
The research area is located in the eastern part of Langgun Island, Langkawi, Malaysia. Several small islands in the area are included in the research scope, including Anak Tikus Island, Anak Berangan Island, Batang Tunggang Cape, and Langgun Cape. Research on karst geomorphology is still very poor in the research area, especially regarding the classification and the history of the formation. The main motivation for this research is to reveal the beauty and uniqueness of the karst morphology of the research area, which is one of the most valuable geological heritages. Chemical weathering caused by surface water and underground water causes the limestone exposed on this island to form an island karst landscape. The karst morphology in Langgun Island is classified into exokarst and endokarst geomorphology. The morphology of exokarst is divided into two, namely negative exokarst and positive exokarst. The negative exokarst geomorphology found in the study area is dolina and uvala. Meanwhile, the morphology of positive exokarst consists of weathering island karst, which is karst resulting from wave erosion (tombolo, sea stumps, abrasion platforms, sea notches), and residual hills (karst tower and karst cone). The endokarst morphology found is the stalactite feature. This research will be able to increase understanding of karst development so that it forms a unique, beautiful morphology and increases the value of tourism potential, especially in the research area to influence tourist to visit.